#TITLE_ALTERNATIVE# - Mulyani (NIM 205 05 001), Oviyanti
ABSTRACT: Digestion methods are employed for the determination of elements in solids subsequent. The aim of this method is therefore to completely transfer the analytes into solution. This method is very simple but if digestion technique used is not complete, the analyses result will be not as accurate. This research tries to compare two digestion methods, used conventional method (hot plate method) and bomb teflon method, where the sample will be heated in the hot plate with beaker glass in 132 oC and digestion bomb teflon method at 190 oC for 120 minutes. The nine element of the result of the digestion process, K, Na, Ca, Mg, Fe, Al, Cr, Cu and Pb are measured using Atomic Absorption Spectroscopy (AAS) method. The eight soil sample used in this research comes from the land along Citarum river, with the variation mass of each sample are 1 and 3 gram, and various volume of HCl and aqua regia. The physical and chemical properties of the samples, that are the content of water, pH, C-organic, total N, C/N ratio, organic substances of the soil, Cation Exchange Capacity, and soil texture, are also analyzed be based on standard procedure. The result of this research show, from nine elements of the research the higher digestion content yield from the 1 gram sample rather than in 3 gram sample, and the digestion process using HCl also yields the higher mass of the digestion process rather than aqua regia. The physical and chemical properties contained from eight soil sample, have variation depend on material places enviromental, otherwise all result from this physical and chemical analysis support to quantitative element from eight soil sample.